Users' Perspective on the Evaluation of Mental Health Services: Experience from a Discharge Program in Argentina - Ardila Gómez, Sara Elena (2014)
Introduction: The inclusion of mental health service users’ perspective in the evaluation of the services contributes both to its validity and to the protection of rights of individuals with mental illness. While the development of evaluations that take into account users’ views is increasing, the practice still lacks diffusion in real-life settings, that is, incorporation in everyday service management practices, especially in developing countries. Objective: Describe and analyze users’ perspective on a discharge program for women in Argentina, with emphasis on the strategies that facilitate the inclusion of their perspective on service evaluation in real life settings in a developing country. Methods: A qualitative study was carried out with fifty-six users of a discharge program associated with a psychiatric hospital in the southern zone of Greater Buenos Aires, from 2011 to 2012. The qualitative methodologies used were participant observation, records analysis, questionnaires, and focus groups. Results: The participative feature of the program, mental health workers’ use of narrative language, and the focus on users’ “everyday life” concerns emerged as variables that promote the inclusion of users’ perspective. Conclusions: Results raise a discussion about the concept of “care” in contrast to “health care.” Consequently, further development of the care component in community mental health services evaluations is proposed.